Analysis on the fulfillment of hierarchy of needs for central region of Malaysia - Mohamed Osman, Mariana; Bachok, Syahriah; Abdullah, Alias; Ibrahim, Mansor; Abu Bakar, Aisyah (American Scientific Publishers, 2017)
Some literature suggested that in less developed countries, the well-being of the residents is higher in urban areas where economic development while in wealthier countries, the well-being of the residents is higher in low-density and rural areas closer to the natural environment. The fulfillment of the survival needs of the population allows the nation to progress to the higher levels of well-being and eventually sustainable well-being. By analyzing the fulfillment of human motivational needs, this paper highlight the differences in the fulfillments of human needs between urban, suburban and rural communities in the most urbanized and populated regions of Malaysia